RELAYOUT LANTAI PRODUKSI SPRINGBED MENGGUNAKAN METODE SLP, CORELAP SERTA SIMULASI PROMODEL, DAN FLEXSIM - Geraldo Tjhindrata; Lamto Widodo; Adianto (Jurnal Ilmiah Teknik Industri, 2023)
PT. Alpha Jaya Manunggal Mandiri is manufacturing company engaged in furniture sector. There are several problems with old layout such high material handling costs, long distances between work stations, and alternating flow. Therefore, relayout and lean manufacturing approach were carried out. Alternative layouts made using SLP method, and CORELAP. The initial steps in making alternative layouts are measuring floor area, making production flows, and measuring production standard times. Next step is forecasting product demand for next 10 years for routing sheet. Routing sheet used to determine number of machines needed to meetproduct demand. Alternative layout was created using 2 methods. Based on alternative layout, material handling costs and moving moments are calculated to find layout with minimum material handling costs and moving moments moments. The selected layout is alternative layout SLP method cause it reduces material handling costs by 50.12%, moving moments by 17.86%, and distance by 53.42%. Then lean manufacturing approach carried out to increase productivity. A simulation was carried out with Promodel and Flexsim software to simulate new and old layout to find product improvements using new layout. Based on Promodel simulation, there was decrease in the average time in system by 21.82%, decrease in the average time in operation by 22.36%, and increase in total production by 15.29%. Based on Flexsim simulation, there was increase in amount of daily production by 58.52%, and decrease in staytime by 33.47% per product. Through research, it can be concluded that layout can be implemented as new layout on springbed production floor.